The sensitivity of communities towards the environmental changes in Tembeling, Pahang and Muar Rivers - Md. Yassin, Sulaiman; Abu Samah, Asnarulkhadi; Abu Samah, Bahaman; Idris, Khairuddin; Hamzah, Azimi; Mohamed Shaffril, Hayrol Azril (Marsland Press, 2013)
Rivers have played a long and significant role in community livelihoods. However, extensive development processes have created formidable challenges that affect the daily activities of those who reside near rivers. The present study attempts to gain a broader understanding of the sensitivity of communities residing near three main rivers in Malaysia in view of the environmental changes that are occurring to the rivers. This is a qualitative study in which a total of three Focus Group Discussions were conducted with the communities that reside near the rivers at Kuala Tembeling, Kuala Pahang and Muar. To achieve the study's objective, data relating to the communities' sensitivity towards the environmental changes, the causes of these changes, their impact on the communities' socio-economic activities and efforts to reduce the impacts were gathered from the respondents. A number of recommendations were made by the respondents and including them in any preservation strategy is crucial to form a holistic approach towards an effective preservation effort.